Perbandingan Algoritma Genetika dengan Algoritma Greedy Untuk Pencarian Rute Terpendek - Rizky Berlia Oktaviandi; M. Sadid Tafsirul Hadi; Alanfansyah Ghozy Santoso; Nova El Maidah (Faculty of Computer Science, University of Jember, 2018)
In everyday life we ​​often travel from place to place. So that we need to consider the time and cost efficient. Therefore, accuracy is needed to determine the shortest path as a consideration in decision to show the path to be taken. The results obtained also require speed and accuracy with the help of a computer. Using or functioning a computer there must be a distributed program in it. The programs contained in the computer vary widely and each program must use an algorithm. Algorithm is a collection of commands to solve a problem gradually from start to finish. There are various algorithms that can be used to find the shortest route such as Breadth First Search algorithm, Depth First Search, A *, Hill Climbing and others. For that required comparison algorithm which is able to find the shortest route accurately and efficiently. In this journal, the algorithm to be compared is the genetic algorithm and greedy algorithm to find the shortest route on a map. Some aspects to be compared are aspects of the accuracy, speed, and complexity of genetic algorithms and greedy algorithms for the shortest route search.